2021
DOI: 10.3390/clockssleep3030031
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Nights of Moderate Sleep Loss Does Not Affect Mood in Healthy Young Males

Abstract: Sleep loss causes mood disturbance in non-clinical populations under severe conditions, i.e., two days/nights of sleep deprivation or a week of sleep restriction with 4–5 h in bed each night. However, the effects of more-common types of sleep loss on mood disturbance are not yet known. Therefore, the aim of this study was to examine mood disturbance in healthy adults over a week with nightly time in bed controlled at 5, 6, 7, 8 or 9 h. Participants (n = 115) spent nine nights in the laboratory and were given e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Notably these results were consistent across Morning, Afternoon or Evening testing- implying that circadian influences on mood are weak or absent when sleep is restricted, although no assessment were obtained during the nighttime. Consistent with this there were no time-of-day effects in a similar 5-h restriction study reported recently by Harous et al (2021) , but in their case only Fatigue-Inertia, but no other aspects of negative mood increased. Other studies, also using PANAS (e.g., Saksvik-Lehouillier et al, 2020 ) show no effect of sleep restriction (2 h less than normal sleep duration) on Negative Affect, but, as in our own work, a reduction in Positive Affect.…”
Section: Introductionsupporting
confidence: 90%
“…Notably these results were consistent across Morning, Afternoon or Evening testing- implying that circadian influences on mood are weak or absent when sleep is restricted, although no assessment were obtained during the nighttime. Consistent with this there were no time-of-day effects in a similar 5-h restriction study reported recently by Harous et al (2021) , but in their case only Fatigue-Inertia, but no other aspects of negative mood increased. Other studies, also using PANAS (e.g., Saksvik-Lehouillier et al, 2020 ) show no effect of sleep restriction (2 h less than normal sleep duration) on Negative Affect, but, as in our own work, a reduction in Positive Affect.…”
Section: Introductionsupporting
confidence: 90%